Studies on the correlation between mutation and integration of HBV in hepatocellular carcinoma. Issue 8 (21st August 2020) - Cui, Xiaofang; Wei, Wei; Wang, Chao; Qi, Yanwei; Qin, Xiao; Huang, Lizhen; Li, Weiyang
Abstract: It is well known that both the mutation and integration of the Hepatitis B virus (HBV) are of great significance in liver cancer, however, the relationship between mutation and integration is still unclear. In the present study, sequencing data from 426 previously published samples were analyzed and 5374 specific HBV mutations in cancer tissues were discovered. By comparing integrated samples and non-integrated samples, we found that the integrated samples had higher sample single nucleotide variants (SNVs) positive rates and SNV numbers, as well as higher sample frequency of SNV in the X region of the HBV genome. Samples with HBV integration in the telomerase reverse transcriptase (TERT) region showed higher SNV positive rates and numbers than samples without integration. Moreover, the SNVs (209 [T>G] and 531 [T>C; T>G]) were seen with higher frequency in samples with integration in the TERT region. Our study showed that the occurrence of viral integration events is closely related to the occurrence of SNV, and SNV in the X region should be more directly associated with viral integration. The present study provides an initial exploration of the relationship between HBV mutation and integration to help improve our understanding of the relationship between viral integration and mutation.